The epidemiology of United States high school basketball injuries, 2005-2007 - Borowski, L. A.; Yard, E. E.; Fields, S. K.; Comstock, R. D. (The American Journal of Sports Medicine, 2008)
With more than a million high school athletes playing during the 2006-2007 academic year, basketball is one of the most popular sports in the United States.